The Learning Management For Children With Special Needs (Study In Efata PAUD, Semarang City) - Arzaqi, Roby Naufal; Diana, Diana (BELIA: Early Childhood Education Papers, 2019)
This study aims to describe the management of learning for children with special needs in EFATA PAUD (Early Childhood Education), Semarang. In addition, this study also aims to determine the supporting and inhibiting factors in learning in the EFATA PAUD, Semarang. The method in this research is descriptive qualitative research method with a case study design based on the theory of Ley Kekeh Marthan. Data collection is carried out through interviews, observation and documentation techniques. Observations are made to find out the phenomena associated with the management of learning in the classroom starting from the preliminary activities to the final activities. The observations are followed up by interviewing educators in the EFATA PAUD. The documents collected function as supporting data. Then the validity of the data is seen using triangulation. The results of the analysis of the data that the management of learning for children with special needs in PAUD EFATA Semarang City is related to learning planning, organizing, managing, and evaluating learning that refers to Ley Kekeh Martan's theory in the book on Inclusive Education Management and PAUD standards in Permendikbud No. 137 of 2014. Learning planning includes the application of the 2013 PAUD curriculum, area learning models, practice-based learning methods, visual learning media, and classroom settings based on safety and comfort aspects of play. Organizing includes carrying out the duties and responsibilities of teaching staff and education staff. The management is in the form of supervision and management of school and community relations. The evaluation includes the results of the process and learning outcomes, structured follow-up in the annual program. The management of this learning is also influenced by supporting factors in the form of guidance, and the provision of information from the HIMPAUDI (Association of Early Childhood Education in Indonesia) of Semarang City, the commitment of teachers and parents to support the achievement of institutional goals. Inhibiting factors are the unavailability of adequate facilities including the place of implementation of activities, not having private land, and institutional permits. Keywords: Learning Management, Children with Special Needs, PAUD EFATA.